Recovered Spent Engine Oil Treatment By Using Silica Gel Filtration Technique - Nasir, Nurfarah Azlin Mohd (2024)
Recycling spent engine oil is essential for supporting sustainable environmental, economic, and health concerns arising from improper disposal. This research explores the effectiveness of using ultrafine filter cloth and silica gels during filtration of spent engine oil under ambient temperature. The experimental conditions influencing the pH, density, viscosity and color appearance were mass of silica gels and working volume for the spent engine oil. The spent engine oil were characterized in terms of physical and chemical characteristics including SEM, AFM, FTIR and DSC. One factor at a time approach (OFAAT) was adopted to control certain variables while other variables were varied during the experimental work. Results have shown that oil's visual clarity, density, pH, viscosity, and chemical composition were improved by the use of ultrafine filter cloth. They effectively removed particulate matter, contaminants, and impurities, resulting in a lighter color, reduced density, increased pH, and decreased viscosity of the filtered engine oil (FEO). SEM analysis of the filter cloth pre- and post-filtration revealed substantial accumulation of contaminants, demonstrating the cloth's efficacy in trapping impurities. The filtered engine oil assisted with silica gels (SG FEO) exhibited greater improvements, including a further lightened color, lower density (0.77 g/cm³), pH closer to fresh engine oil (6.694), and reduced viscosity (32.3 cSt), aligning it closely with the properties of fresh engine oil. FT-IR analysis showed the significant reduction of acidic and aromatic compounds, indicating effective removal of contaminants. DSC analysis revealed a lower melting point for SG FEO, comparable to fresh engine oil,confirming the improved thermal properties post-filtration. SEM and topographical analysis of the silica gels pre- and post-filtration highlighted their role in absorbing contaminants, evidenced by increased surface roughness and the presence of hydrocarbons and aromatic compounds on the silica gel surfaces post-filtration. These findings proven the the ability of advanced filtration techniques in enhancing the quality and recyclability of spent engine oil, potentially leading to better engine performance, reduced wear, and improved environmental sustainability.